2008
DOI: 10.1002/jcla.20217
|View full text |Cite
|
Sign up to set email alerts
|

Acute phase phospholipids related to the cardiolipin of mitochondria in the sera of patients with chronic fatigue syndrome (CFS), chronic ciguatera fish poisoning (CCFP), and other diseases attributed to chemicals, Gulf War, and marine toxins

Abstract: This study examined 328 CFS sera in a study with 17 CCFP, 8 Gulf War Veterans (GWV), 24 Prostate Cancer (PC), and 52 normal sera in the modified Membrane Immunobead Assay (MIA) procedure for CTX. Three hundred and twenty-eight CFS patients' sera were examined by the modified MIA with purified MAb-CTX and 91.2% gave a titre > or =1:40. 76% of the 17 CCFP sera samples and 100% of the 8 GWV sera samples also had a titre > or =1:40. 92.3% of 52 normal sera showed titres of 1:20 or less, while 4 gave titres of > or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…CFS subjects had serum lipid fractions that resembled those commonly found in patients poisoned with ciguatoxin, a marine toxin [13]. Sera from patients with CFS, chronic ciguartera fish poisoning (CCFP), gulf war veterans (GWV), and prostate cancer patients contained antibodies to cardiolipin (aCL), a phospholipid of the mitochondrial membrane [13]. Further study found that 95% of CFS patients had anticardiolipin antibody (ACA) of the IgM subtype, 10% showed an IgG response, 2.5% had an IgA response; 4 patients were positive for IgG and IgM, and one patient was positive for all three antibody subtypes [12].…”
Section: Immune Responsementioning
confidence: 85%
“…CFS subjects had serum lipid fractions that resembled those commonly found in patients poisoned with ciguatoxin, a marine toxin [13]. Sera from patients with CFS, chronic ciguartera fish poisoning (CCFP), gulf war veterans (GWV), and prostate cancer patients contained antibodies to cardiolipin (aCL), a phospholipid of the mitochondrial membrane [13]. Further study found that 95% of CFS patients had anticardiolipin antibody (ACA) of the IgM subtype, 10% showed an IgG response, 2.5% had an IgA response; 4 patients were positive for IgG and IgM, and one patient was positive for all three antibody subtypes [12].…”
Section: Immune Responsementioning
confidence: 85%
“…In the effort to develop biomarkers, progress has been made particularly in animal studies [112,113,114,115,116]. In humans, attempts have been made to identify CTX in human blood [335] and other potential markers of effect of CTX exposure [336,337,338], but studies are needed with larger sample sizes, clearly delineated case definitions, confirmatory fish testing across laboratories with appropriate blinding, and replication of candidate biomarkers across multiple study populations.…”
Section: Future Directionsmentioning
confidence: 99%
“…In some cases patients may present with structural deformities in the mitochondria, these include subsarcolemmal mitochondrial aggregates, compartmentalization of the internal mitochondrial membrane and polymorphism (Plioplys and Plioplys, 1995). Similarly defective mitochondrial metabolic activity may be characterised by the presence of neurotoxic phospholipids and phospholipids of mitochondria that appear after microbial infections (Hokama et al, 2008). Neutrophil in the innate immune system employ respiratory burst and oxidative phosphorylation as a means to effectively kill and clear pathogen invasion.…”
Section: Other Cellular Processesmentioning
confidence: 99%